Formation of the structure of psychophysiological features of elite basketball players - Xiang-Qian Xu; Lesia Korobeinikova; Xu Li; Mischuk Diana; Georgiy Korobeynikov; Wei Han; Uriy Sergienko (Kharkiv State Academy of Physical Culture, 2023)
Among coaches and scientists, one of the main topics is the improvement of the system for training elite athletes. Traditional studies in basketball devoted to the actual connection of study with a long training process. Training and competitive activity in basketball includes neurodynamic, psychomotor, cognitive and psychoe-motional characteristics. Modern research devoted to the characteristics of the functional states of athletes in various training and competitive conditions. But among the modern studies of team sports, there are no data on the psychophysiological states of elite athletes for different types of monitoring. Purpose: Development of the system of psychophysiological support of elite basketball players as an actual scientific direction in the theory and methodology of sports training Materials and methods: The 13 elite basketball players, age 19-23 (sport experience more than 8 age) were examined. The sensory-motor response, mobility and balance of nervous process, verbal memory, operative thinking and general intelligence were studied. All of tests include the complex of computer diagnostic "Multipsychometer 05". Also, in battery were include tests: estimates of actual psychical state (by color test Lusher), field independence (by Stroop test), motivation (by Mehrabian test) and aggressive (by Bass-Darki test). With the factors analysis the main components of psychophysiological characteristics of basketball players were obtained. Results: The factor's structure of psychophysiological state of elite basketballs included 4 factors: neurodynamics, cognitive resources, energy-information and emotional-cognitive. Conclusion: The factor structure of psychophysiological state of elite basketball players was revealed. The identified factors can be used to correct the training process of elite athletes.